NO emission of co-combustion coal and biomass blends in an oxygen-enriched atmosphere. Issue 23 (1st December 2016) - Pu, Ge; Wang, Wending; Peng, Ruixiang; Zhu, Weilin; Zhao, Fangyuan; Fu, Fanxuan; Long, Yun
ABSTRACT: A fixed-bed combustion system was used to study the NO emission characteristics of co-combustion of biomass and coal in an O2 /CO2 atmosphere. With the concentration of oxygen varied in 21%, 30%, and 40% while the biomass blended proportion mounts raised from zero to 10% then to 30%, the generated NO was classified to Vdaf -NO and FCad -NO, respectively, and the emission rate and conversion ratio of NO were analyzed. The results showed that the NO emission rate and concentration increased with increase in oxygen concentration, but the conversion ratio decreased. Meanwhile, the blended biomass reduced the NO emission concentration and conversion ratio.